Al-Mn composite nanocrystals and its manufacturing method and use
Al-Mn composite nanocrystals, produced through a specific manufacturing process, address the limitations of conventional aluminum adjuvants by simultaneously activating humoral and cellular immunity, offering enhanced immune responses for vaccines and immunotherapies.
Patent Information
- Application Number
- JP2024540049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-28
- Filing Date
- 2022-06-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-06-30
AI Technical Summary
Conventional aluminum adjuvants are unable to simultaneously activate both humoral and cellular immunity, necessitating the development of new adjuvants that can enhance both types of immune responses.
The production of Al-Mn composite nanocrystals is achieved by mixing aluminum and manganese salt solutions with an anionic auxiliary agent, adjusting pH to 5.5 to 8.5, and heating, followed by centrifugal washing and sterilization to stabilize the nanocrystals, which can then be used as vaccine adjuvants.
The Al-Mn composite nanocrystals effectively stimulate both humoral and cellular immunity, providing a robust immune response against pathogens and tumors, and can be used as stable, long-term adjuvants for vaccines and immunotherapies.
Smart Images

Figure 2025501325000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to China Patent Application No. 202111633153.6, filed with the State Intellectual Property Office of the People's Republic of China on December 28, 2021, entitled "Al-Mn composite nanocrystals and their manufacturing method and use," the entire contents of which are incorporated herein by reference.
[0002] The present application relates to the field of vaccine technology, in particular to Al-Mn composite nanocrystals and their preparation and use. [Background technology]
[0003] Aluminum salt adjuvants are the most widely used and safest immune adjuvants among conventional vaccine adjuvants, examples of which include potassium aluminum sulfate, aluminum phosphate, and aluminum hydroxide. Among them, aluminum hydroxide adjuvants are the most widely used. Currently, the immune stimulating mechanism of aluminum adjuvants is mainly interpreted as a "reservoir" effect, promotion of phagocytosis, activation of the proinflammatory pathway NLRP3, etc. Commercially available aluminum hydroxide adjuvants are usually low-crystalline boehmite with a size of 1-10 μm, which generally activates humoral immunity with little T cell-mediated immunity. This is related to the presentation mode of antigens adsorbed by aluminum hydroxide adjuvants. After the micron-order aluminum hydroxide adjuvant adsorbs the antigen, the aluminum adjuvant usually binds to the cell membrane of antigen-presenting cells, such as dendritic cells (DC cells), and induces lipid raft formation, causing activation of downstream pathways, which cannot affect the fate of the antigen it presents in the cell, but the antigen is presented through the major histocompatibility complex II (MHC-II) and not cross-presented through the major histocompatibility complex I (MHC-I) after being processed by the lysosomal pathway. However, recent research has shown that to meet the demands of more common pathologies, it is not only necessary to trigger humoral immunity to produce antibodies that neutralize pathogenic microorganisms, but also to eliminate viruses, bacteria, or abnormal physiological responses through T cell-mediated immunity, and generate memory T cells to prevent and protect the body. Therefore, a new type of aluminum adjuvant formulation or composite adjuvant is needed to meet the demands of preventive vaccine protection.
[0004] Since aluminum adjuvants have the advantages of safety and convenience during long-term use, as well as the convenience of antigen and molecular adjuvant carriers, the new adjuvants formed by combining aluminum salts and molecular adjuvants have become the main trend in the development of new adjuvants. For example, the composite adjuvants formed by aluminum salts and 3M-052, CpG and TLR agonists have shown further advantages in improving the antibody titer and cellular immunity of vaccines. However, the pre-preparation of molecular adjuvants and compounding with aluminum adjuvants require many procedures, which are likely to greatly affect the efficacy of the new adjuvants. Therefore, developing aluminum adjuvants with the characteristics of convenient production, sustained release of carriers and antigens, and high safety can make up for the shortage of aluminum adjuvants in the lack of cellular immunity. In addition, the new composite adjuvants that are easy to manufacture and produce are of more practical value. Summary of the Invention [Problem to be solved by the invention]
[0005] The present application has been made in view of the above circumstances, and provides an Al-Mn composite nanocrystal, which can effectively solve the technical problem that conventional aluminum adjuvants cannot simultaneously activate humoral immunity and cellular immunity, as well as a method for producing and using the same. [Means for solving the problem]
[0006] One aspect of the present application provides a method for producing Al-Mn composite nanocrystals, the method including: step 1 of mixing an aluminum salt solution, a manganese salt solution, and an anionic auxiliary solution to obtain a mixture, and adjusting the pH of the mixture to 5.5 to 8.5; and step 2 of heating the mixture to cause a reaction, and washing the obtained solid product to obtain Al-Mn composite nanocrystals.
[0007] Specifically, in step 1, the pH of the mixture is adjusted with an acidity / alkali regulator. The acidity / alkali regulator may be an alkaline solution and / or an acid solution. The alkaline solution and the acid solution are ordinary pH adjusting solutions, and the concentration of the alkaline solution is 0.01 to 1 mol / L, preferably 0.05 to 0.6 mol / L. The alkaline solution is one or more of an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous ammonia solution, an aqueous sodium hydrogen carbonate solution, and an aqueous sodium phosphate solution. The concentration of the aqueous sodium hydroxide solution is 0.05 to 1 mol / L, preferably 0.3 to 0.6 mol / L.
[0008] Specifically, the pH of the mixture is adjusted because the Al-Mn composite nanocrystals obtained within that range are so stable that their crystal form does not change even when sterilized. Specifically, the phosphate of the sodium phosphate aqueous solution is Na 2 HPO 4 And / or Na 3 PO 4 It is.
[0009] Specifically, in step 1, the molar ratio of the total solutes of the aluminum salt solution, the manganese salt solution, and the anionic assistant solution to the solutes of the alkaline solution is 1: (1 to 6). For example, the molar ratio of the total solutes of the aluminum salt solution, the manganese salt solution, and the anionic assistant solution to the alkaline solution NaOH is 1: (1 to 6). Preferably, the molar ratio of the total solutes of the aluminum salt solution, the manganese salt solution, and the anionic assistant solution to the solutes of the alkaline solution is 1: (2 to 4). For example, the molar ratio of the total solutes of the aluminum salt solution, the manganese salt solution, and the anionic assistant solution to the alkaline solution NaOH is 1: (2 to 4). Specifically, in step 1, the pH value of the mixture is 5.5 to 8.0. Preferably, the pH value of the mixture is 6.0 to 7.0.
[0010] Specifically, in step 1, the aluminum salt solution, the manganese salt solution, and the anionic auxiliary solution are mixed by stirring while dropping the solutions. The dropping speed of the aluminum salt solution, the manganese salt solution, and the anionic auxiliary solution is 2 to 15 mL / min, and preferably 3 to 8 mL / min. The stirring speed during the mixing is 50 to 1000 rpm, and preferably 300 to 800 rpm. The stirring time during the mixing is 1.5 to 10 hours, and preferably 1 to 5 hours.
[0011] Specifically, when adjusting the pH value of the mixture with an alkaline solution, the dropping speed of the alkaline solution is 0.5 to 10 mL / min, and preferably 1 to 4 mL / min.
[0012] Specifically, in step 2, the mixture is centrifuged and washed with NaCl solution to remove unreacted free ions and desorbed anionic auxiliary, and then redissolved and dispersed in NaCl solution. After sterilization at 121°C for 30 to 60 minutes by wet heat sterilization, the mixture is dispensed to obtain Al-Mn composite nanocrystals. The Al-Mn composite nanocrystals can be stored in a refrigerator (2 to 8°C). Here, the centrifugation speed of the centrifugation washing is 2000 to 10000g, the centrifugation time of the centrifugation washing is 1 to 100 minutes, and the number of washings of the centrifugation washing is 2 to 5 times. Preferably, the centrifugation speed of the centrifugation washing is 4000 to 8000g, the centrifugation time of the centrifugation washing is 5 to 20 minutes, and the number of washings of the centrifugation washing is 2 to 3.
[0013] Specifically, the concentration of the NaCl solution is 0.1% to 1.5%. Preferably, the concentration of the NaCl solution is 0.15% to 0.8%.
[0014] In another embodiment, the solute of the aluminum salt solution is one or more selected from the group consisting of aluminum chloride, aluminum sulfate, aluminum nitrate, and aluminum acetate. The solvent of the aluminum salt solution is one or more selected from the group consisting of sodium acetate solution, physiological saline, water, and ethanol. Specifically, the concentration of the solvent of the aluminum salt solution is 0.01-1 mol / L, and the concentration of the sodium acetate solution is 0.03-0.07 mol / L.
[0015] In another embodiment, the solute of the manganese salt solution is one or more selected from the group consisting of manganese chloride, manganese sulfate, manganese nitrate, and manganese acetate, and the solvent of the manganese salt solution is one or more selected from the group consisting of water, saline, and ethanol. In another embodiment, the solute of the anionic auxiliary solution is an organic acid salt and / or an amino acid, and the solvent of the anionic auxiliary solution is one or more selected from the group consisting of water, saline, and ethanol.
[0016] Specifically, the anionic auxiliary solution can fully realize the compounding effect of the anionic auxiliary and the metal ions (aluminum and manganese). For the pre-precipitate in the mixture, the heat treatment promotes the uniform growth and crystal formation of the pre-precipitate in the mixture, improving the sterilization stability. Then, after centrifugal sedimentation, washing, and sterilization, Al-Mn composite nanocrystals are obtained.
[0017] Specifically, the anionic auxiliary is an organic material containing polyhydroxyl group, carboxyl structure, and phosphorus element. The anionic auxiliary in the present application can form a stable compound with both aluminum ion and manganese ion, and is an ideal auxiliary used to stabilize and adjust the particle size and distribution of Al-Mn composite nanocrystals.
[0018] In another embodiment, the organic acid salt is citric acid and / or salicylic acid, and the amino acid is one or more selected from the group consisting of cysteine, cystine, tyrosine, aspartic acid, and glutamic acid.
[0019] In another embodiment, the molar ratio of aluminum element in the aluminum salt solution to manganese element in the manganese salt solution in the mixture is 1: (0.05-1). Preferably, the molar ratio of aluminum element in the aluminum salt solution to manganese element in the manganese salt solution is 1: (0.1-0.5). The ratio of the concentration of the anionic auxiliary to the total concentration of metal ions is (0.1-10):1. Preferably, the ratio of the concentration of the anionic auxiliary to the total concentration of metal ions is (0.3-3):1. Here, the total concentration of metal ions is the sum of the concentrations of the aluminum salt solution and the manganese salt solution.
[0020] Specifically, the aluminum salt solution has a concentration of 0.01 to 1 mol / L, preferably 0.03 to 0.07 mol / L. The manganese salt solution has a concentration of 0.001 to 1 mol / L, preferably 0.003 to 0.05 mol / L. The anionic assistant solution has a concentration of 0.01 to 0.5 mol / L, preferably 0.05 to 0.5 mol / L.
[0021] In another embodiment, in step 2, the heating reaction is carried out at a temperature of 60° C. to 130° C., and the heating reaction time is 0.5 to 20 hours.
[0022] A second aspect of the present application provides an Al—Mn composite nanocrystal, including an Al—Mn composite nanocrystal produced by the above-mentioned production method.
[0023] Specifically, the pH value of the Al-Mn composite nanocrystals before and after sterilization is 5.5-8.5, the particle size of the Al-Mn composite nanocrystals is stable at 20-5000 nm, the adsorption rate of the Al-Mn composite nanocrystals to bovine serum albumin exceeds 1.6 mg, and the Al-Mn composite nanocrystal product thus obtained has excellent dispersibility and stability.
[0024] A third aspect of the present application discloses Al-Mn composite nanocrystals obtained by said preparation method and the use of said Al-Mn composite nanocrystals in the preparation of a vaccine adjuvant, an immune enhancer, a pharmaceutical composition, a drug delivery carrier, or an immunogenic composition.
[0025] Specifically, the Al-Mn composite nanocrystals provided in the present application are used for the manufacture of vaccine adjuvants and immune enhancers for improving innate and / or adaptive immunity. In some embodiments, the Al-Mn composite nanocrystals stimulate the expression of type I interferon and gamma interferon, thereby improving innate and / or adaptive immunity and regulating immune balance. In other embodiments, the Al-Mn composite nanocrystals can promote antigen presentation and increase antibody production levels to improve innate and / or adaptive immunity. In other embodiments, the Al-Mn composite nanocrystals are administered in combination with, in combination with, or consecutively with an immunomodulator to promote activation of multiple immune pathways and improve innate and / or adaptive immunity. The Al-Mn composite nanocrystals according to the present application can also be used as immune enhancers for tumor prevention and / or disease treatment, such as bacterial infection, fungal infection, viral infection, parasitic infection, tumors, and autoimmune diseases.
[0026] The Al-Mn composite nanocrystals according to the present application can also be used as a pharmaceutical composition for the treatment of autoimmune diseases, where the autoimmune diseases are selected from rheumatoid arthritis, type 1 diabetes, psoriasis, systemic lupus erythematosus, and multiple sclerosis. More specifically, when the Al-Mn composite nanocrystals according to the present application are used as a component of a pharmaceutical composition, the pharmaceutical composition contains the Al-Mn composite nanocrystals and a prophylactic / therapeutic agent, both of which are administered to a subject in need thereof, and can be combined with small molecules, immunomodulators such as polypeptides and antibodies, antibody drugs, or polypeptide drugs by mixing, sequential administration, and modification / denaturation.
[0027] Specifically, the drug delivery carrier includes a composition in which Al-Mn nanocrystals are combined with one or more liquid, solid or commonly used pharmaceutical auxiliaries and / or any auxiliary ingredients, including pharma- ceutically acceptable emulsions, microemulsions, solutions, suspensions, syrups, inert diluents, wetting agents, emulsifiers and dispersants.
[0028] A fourth aspect of the present application provides an antitumor pharmaceutical composition comprising the Al-Mn composite nanocrystal and a therapeutic agent for an antitumor disease.
[0029] Specifically, the present invention provides an application of the antitumor pharmaceutical composition in the treatment of solid and non-solid tumors. The solid tumors include lung cancer, gastric cancer, breast cancer, liver cancer, pancreatic cancer, skin cancer, oral cancer, esophageal cancer, malignant melanoma, head and neck cancer, sarcoma, bile duct cancer, bladder cancer, kidney cancer, colon cancer, placental choriocarcinoma, cervical cancer, ovarian cancer, testicular cancer, uterine cancer, leukemia, etc. The non-solid tumors include glioma, hematoma, etc.
[0030] Specifically, the therapeutic agent for anti-tumor diseases is a small molecule, polypeptide, and antibody-based drug for anti-tumor, such as one or more of PD-L1 antibody, trastuzumab, metformin (Met), paclitaxel, doxorubicin, cisplatin, asparaginase, rituximab, gefitinib, triptorelin, docetaxel, doxorubicin, and fluorouracil.
[0031] A fifth aspect of the present application provides a vaccine composition comprising an antigen and said Al-Mn composite nanocrystals.
[0032] Specifically, the vaccine composition is a protein vaccine and / or an inactivated vaccine, such as an influenza vaccine strain recombinant antigen, a Hepatitis B recombinant antigen, or a varicella zoster virus recombinant protein vaccine, a novel coronavirus subunit protein vaccine, or a novel coronavirus inactivated vaccine.
[0033] Specifically, the antigen in the vaccine composition is derived from a virus, a bacterium, a parasite, and a tumor neoantigen. For example, the virus is selected from DNA and RNA viruses. Preferably, the virus is selected from the group consisting of Coronaviridae, Herpesviridae, Rhabdoviridae, Filoviridae, Orthomyxoviridae, Paramyxoviridae, Picornaviridae, Hepadnaviridae, Flaviviridae, Papillomaviridae, Poxviridae, and Retroviridae. More preferably, the virus is selected from the group consisting of a novel coronavirus, influenza virus, herpes simplex virus, vesicular stomatitis virus, vaccinia virus, HIV, and HBV. For example, the bacteria is selected from gram-positive and gram-negative bacteria. Preferably, the bacteria is selected from the group consisting of Streptococcus pneumoniae, Haemophilus influenzae, Salmonella enterica, Neisseria meningitidis, Staphylococcus epidermidis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Enterobacter cloacae, Citrobacter freundei, Pseudomonas aeruginosa, and Acinetobacter baumannii, Mycobacterium tuberculosis, and Helicobacter pylori.
[0034] More specifically, the antigens in the vaccine composition are derived from a variety of forms of antigens, such as influenza virus, alpha or beta coronavirus (e.g., novel coronavirus and variants), hepatitis virus (e.g., hepatitis A virus, hepatitis B virus), poliovirus, rabies virus, HPV virus, encephalitis virus (e.g., Japanese encephalitis virus), mumps virus, rubella virus, tetanus virus, pertussis virus, diphtheria virus, leprae virus, tuberculosis virus, meningococcus, pneumococcus, and any combination thereof, including live viral / bacterial forms, live attenuated viral / bacterial forms, and subunit proteins, recombinant proteins, or chimeric proteins.
[0035] Specifically, the water used in this application may be ultrapure water and / or water for injection. Manganese is a trace element essential for human growth, metabolism, neuronal function, and antioxidant defense processes. The combination of two inorganic elements, aluminum and manganese, into a composite adjuvant preserves the "reservoir" effect, promotion of phagocytosis, and activation of the proinflammatory pathway NLRP3, which are mediated by the aluminum adjuvant itself. 2+ The innate and adaptive immunity mediated by the α-amino acid are complemented, and the demand for both humoral and cellular immunity to resist infectious pathogens is met. In addition, the manufacturing method of the present application makes it possible to prepare Al-Mn composite nanocrystals with uniform size and controllable morphology.
[0036] Thus, the present application discloses aluminum-manganese composite nanocrystals that can be used as vaccine adjuvants, with simple process, uniform composition, stable structure, long-term storage after sterilization, and convenient use, and can simultaneously activate humoral immunity and cellular immunity, providing a better immune barrier for the prevention of infectious bacteria or viruses. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a transmission electron microscope image of the Al-Mn composite nanocrystals (AlMn-001) provided in Example 1 of the present application. [Diagram 2] FIG. 2 is a transmission electron microscope image of the Al-Mn composite nanocrystals (AlMn-002) provided in Example 2 of the present application. [Diagram 3] FIG. 3 is a transmission electron microscope image of the Al-Mn composite nanocrystals (AlMn-003) provided in Example 3 of the present application. [Figure 4] FIG. 4 shows the XRD results of the Al—Mn composite nanocrystals provided in Examples 1 to 3 of the present application. [Diagram 5] FIG. 5 is a diagram showing the DC activation effect of different ratios of Al-Mn composite nanocrystals provided in Examples 1 to 3 of the present application. [Figure 6]FIG. 6 shows fluorescence imaging images of DC cell endocytosis after binding of the Al-Mn composite nanocrystals (AlMn-003) provided in Example 3 of the present application or a commercially available aluminum adjuvant with an antigen. [Figure 7] FIG. 7 is a graph showing the experimental results of antibody titers after intramuscular injection of the Al-Mn composite nanocrystals (AlMn-003) provided in Example 3 of the present application or a commercially available aluminum adjuvant in combination with OVA antigen into mice. [Figure 8] Figure 8 shows the antibody titer results of mice immunized with the Al-Mn composite nanocrystals provided in Examples 1 to 3 of the present application in combination with a novel coronavirus RBD recombinant protein antigen. [Figure 9] FIG. 9 shows the experimental results of antibody titers after intramuscular injection of the Al-Mn composite nanocrystal (AlMn-003) provided in Example 3 of the present application or the commercially available aluminum adjuvant Alum in combination with H1N1-HA antigen into mice. [Figure 10] FIG. 10 shows the expression results of IFN-γ in mouse splenocytes on day 56 after immunization with the Al-Mn composite nanocrystals AlMn-003 provided in Example 3 of the present application in combination with H1N1 HA antigen. [Figure 11] FIG. 11 shows the results of cytokines in mouse splenocytes on day 56 after immunization with Al-Mn composite nanocrystals AlMn-003 provided in Example 3 of the present application in combination with H1N1-HA antigen. [Figure 12] FIG. 12 is a diagram showing the percentage of memory B cells in the spleen and lung of mice on day 56 after immunization with the Al-Mn composite nanocrystals AlMn-003 provided in Example 3 of the present application in combination with H1N1-HA antigen. [Figure 13] FIG. 13 is a diagram showing the percentage of memory T cells in the spleen of mice on day 56 after immunization with the Al-Mn composite nanocrystals AlMn-003 provided in Example 3 of the present application in combination with H1N1-HA antigen. [Figure 14]Figure 14 is a graph showing the results of enhancing the antitumor effect of a living body using the Al-Mn composite nanocrystal AlMn-001 provided in Example 1 of the present application as an immune enhancing agent, in which the three figures are Figure 14A, Figure 14B, and Figure 14C from left to right, respectively. [Figure 15] FIG. 15 is a graph showing the results of enhancing the anti-distant tumor effect of a living body using the Al-Mn composite nanocrystal AlMn-002 provided in Example 2 of the present application as an immune enhancing agent. [Figure 16] FIG. 16 is a graph showing the results of enhancing the anti-liver cancer effect in a living body using the Al-Mn composite nanocrystal AlMn-003 provided in Example 3 of the present application as an immunopotentiator. [Figure 17] FIG. 17 is a graph showing the results of enhancing the anti-metastatic tumor effect in a living body using the Al-Mn composite nanocrystal AlMn-001 provided in Example 1 of the present application as an immune enhancing agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] In this application, in order to solve the technical defect that conventional aluminum adjuvants cannot simultaneously activate humoral immunity and cellular immunity, Al-Mn composite nanocrystals and their preparation method and use are provided.
[0039] The technical solution of the present invention will be described more clearly and comprehensively in the following with reference to the examples of the present invention, but it is clear that the examples described are only a part of the embodiments of the present invention, and do not include all the embodiments. All other examples obtained by those skilled in the art based on the embodiments of the present invention without creative labor shall be within the protection scope of the present invention. The raw materials or reagents used in the following examples are either commercially available or home-made. EXAMPLES
[0040] Example 1 In the examples of the present application, an Al-Mn composite nanocrystal AlMn-001 was provided, which was produced by a specific production method including the following steps.
[0041] (1) AlCl 3 6H 2 10 was weighed and dissolved in 0.01 mol / L NaAc to prepare an aluminum salt solution with an aluminum ion content of 1 mol / L. 2 4H 2 O was weighed and dissolved in water for injection to prepare a manganese salt solution with a manganese ion content of 0.1 mol / L. Salicylic acid was weighed and dissolved in pure water to prepare an anionic auxiliary solution with a content of 0.05 mol / L. NaOH was weighed and dissolved in water for injection to prepare an alkaline solution with a content of 0.1 mol / L.
[0042] (2) First, the aluminum salt solution and the manganese salt solution were mixed in equal volumes to obtain a mixed solution. 30 mL of the mixed solution was added to 50 mL of the salicylic acid solution at a rate of 10 mL / min. Then, the mixture was stirred at a speed of 1000 rpm for 3 hours to allow the mixing reaction to occur sufficiently, and a mixture was obtained.
[0043] (3) The mixture was stirred at room temperature at 600 rpm, and 30 mL of ammonia solution was added at a rate of 12 mL / min. After the dropwise addition was completed, the pH value of the mixture was adjusted to 7.6, and the temperature was raised to 100°C and heated for 1 hour.
[0044] (4) The mixture was cooled to room temperature and centrifuged at 6000g for 20 minutes. The solid product was washed twice with 0.5% sodium chloride solution. It was also centrifuged at 6000g for 10 minutes and redissolved in 0.5% sodium chloride solution to obtain Al-Mn composite nanocrystals, designated AlMn-001. The mixture was then sterilized at 121°C for 30 minutes with moist heat, and then packaged separately.
[0045] (5) The Al-Mn composite nanocrystals were stored refrigerated (2–8 °C) for a long period of time. Referring to Figure 1, Figure 1 shows the size and morphology of the Al-Mn composite nanocrystals prepared in Example 1 of the present application measured by a transmission electron microscope (FEI Company, model number Tecnai G2 20S-TWIN). From Figure 1, it can be seen that the Al-Mn composite nanocrystals prepared in Example 1 of the present application are composite particles in which thin sheet-like nanosheets with a width of 30-120 nm and a length of 50-300 nm are deposited. Example 2
[0046] In the examples of the present application, an Al-Mn composite nanocrystal AlMn-002 is provided, which is produced by a specific production method including the following steps.
[0047] (1) Al(NO 3 ) 3 6H 2 Mn(SO) was weighed and dissolved in 0.01 mol / L NaAC to prepare an aluminum salt solution with an aluminum ion content of 0.4 mol / L. 4 ) 2 4H 2 O was weighed and dissolved in water for injection to prepare a manganese salt solution with a manganese ion content of 0.1 mol / L. Glutamic acid was weighed and dissolved in pure water to prepare an anionic auxiliary solution with a concentration of 0.20 mol / L. KOH was weighed and dissolved in water for injection to prepare an alkaline solution with a KOH content of 0.5 mol / L.
[0048] (2) First, the aluminum salt solution and the manganese salt solution were mixed in equal volumes to obtain a mixed solution. 40 mL of the mixed solution was added to a container containing 30 mL of an aqueous glutamic acid solution, and the mixture was reacted at room temperature with a stirring speed of 800 rpm for 7 hours to allow the complex reaction to occur sufficiently, and a mixture was obtained.
[0049] (3) The rotation speed was adjusted to 500 rpm for stirring, then potassium hydroxide solution was added at a rate of 6.9 mL / min so that the pH of the solution was 8.5, the temperature was adjusted to 80° C., and the reaction was maintained for 7 hours.
[0050] (4) After cooling to room temperature, the mixture was centrifuged at 6000g for 20 minutes, and the solid product was washed twice with 0.5% sodium chloride solution, centrifuged at 6000g for 10 minutes, and redissolved in 0.5% sodium chloride solution to obtain Al-Mn composite nanocrystals, designated as AlMn-002.
[0051] (5) After that, they were sterilized with moist heat at 121 °C for 30 minutes, and then packaged separately. The Al-Mn composite nanocrystals were stored refrigerated (2-8 °C) for a long period of time. Referring to Figure 2, Figure 2 shows the size and morphology of the Al-Mn composite nanocrystals prepared in Example 2 of the present application measured by a transmission electron microscope (FEI Company, model number Tecnai G2 20S-TWIN). From Figure 2, it can be seen that the Al-Mn composite nanocrystals prepared in Example 2 of the present application are composite particles in which thin sheet-like nanosheets with a width of 20-70 nm and a length of 30-100 nm are deposited. Example 3
[0052] In the examples of the present application, Al-Mn composite nanocrystals AlMn-003 were provided by a specific manufacturing method including the following steps.
[0053] (1) Aluminum acetate was weighed and dissolved in 0.01 mol / L NaAC to prepare an aluminum salt solution with an aluminum ion content of 0.5 mol / L. 2 4H 2 O was weighed and dissolved in water for injection to prepare a manganese salt solution with a manganese ion content of 0.1875 mol / L. Citric acid was weighed and an anionic auxiliary solution with a concentration of 0.1 mol / L was prepared. Sodium hydroxide was weighed and dissolved in water for injection to prepare an alkaline solution with a content of 0.2 mol / L.
[0054] (2) First, the aluminum salt solution and the manganese salt solution were mixed in equal volumes to obtain a mixed solution. 10 mL of the mixed solution was added to a reactor containing 50 mL of citric acid solution, and mixed at room temperature at 1200 rpm for 1 hour to fully react with each other, thereby obtaining a mixture.
[0055] (3) Next, 10 mL of an aqueous sodium hydroxide solution was added dropwise at a rate of 16.9 mL / min to adjust the pH of the solution to 9, and the temperature was raised to 60° C. and the reaction was maintained for 12 hours.
[0056] (4) After cooling to room temperature, the mixture was centrifuged at 8000g for 10 minutes, and the solid product was washed three times with 0.5% sodium chloride solution, centrifuged at 8000g for 10 minutes, and redissolved in 0.5% sodium chloride solution to obtain Al-Mn composite nanocrystals, designated as AlMn-003.
[0057] (5) After that, they were sterilized with moist heat at 121 °C for 30 minutes, and then packaged separately. The Al-Mn composite nanocrystals were stored refrigerated (2-8 °C) for a long period of time. Referring to Fig. 3, Fig. 3 shows the size and morphology of the Al-Mn composite nanocrystals prepared in Example 3 of the present application measured by a transmission electron microscope (FEI Company, model number Tecnai G2 20S-TWIN). From Fig. 3, it can be seen that the Al-Mn composite nanocrystals prepared in Example 3 of the present application are composite particles in which thin sheet-like nanosheets with a width of 20-100 nm and a length of 30-200 nm are deposited. Example 4
[0058] The examples of the present application provide the measurement results of the physicochemical properties of the Al-Mn composite nanocrystals obtained in Examples 1 to 3. Specifically, the following measurement tests are included. The following detection method can be applied to measure the physicochemical properties of Al-Mn composite nanocrystals at any Mn:Al molar ratio.
[0059] (1) Characterization of hydrated particle size and potential The Al-Mn composite nanocrystals prepared in Examples 1, 2, and 3 were diluted 100 to 200 times with ultrapure water until they became transparent and colorless, and 800 μL of the diluted solution was placed in a Zeta potential sample cell and tested.
[0060] (2) X-ray diffraction (XRD) characterization The Al-Mn composite nanocrystals were loaded into a centrifuge tube, and after freeze-drying, the solid powder was evenly filled into the window of the glass sample stand, and then pressed with a slide to spread the convex part flat, so that the powder filled the entire concave window and was flush with the top surface of the slide glass. The sample stand was placed in the X-ray diffraction instrument, and the parameters were set in the software to scan. The results are shown in Figure 4. It was found from Figure 4 that the manganese contained in the Al-Mn composite nanocrystal samples obtained in Examples 1 to 3 of the present application was of trimanganese tetroxide crystal type, and the aluminum was of AlO(OH) crystal type.
[0061] (3) Digestion quantification of Al-Mn composite nanocrystals 100μL of the Al-Mn composite nanocrystals obtained in Examples 1-3 of the present application diluted 10-fold with ultrapure water was collected and placed in a 50mL polytetrafluoroethylene digestion bottle, 2-3mL of MOS grade concentrated nitric acid was added, the temperature was raised to 90°C on an electric heating plate, and 2mL of MOS grade hydrogen peroxide was added dropwise to make the solution transparent. The temperature was then raised to 160°C with a gradient of 10°C each time and held for 20 minutes, and slowly evaporated until 0.5mL of solution remained, then removed, cooled to room temperature, and volumized to 3g. A 3% washing solution was prepared with MOS grade nitric acid, a calibration curve was created with a standard sample, and detection and quantification were performed using an inductively coupled plasma mass spectrometer.
[0062] (4) Adsorption rate: The adsorption rate was calculated by the adsorption effect of Al-Mn composite nanocrystals on bovine serum albumin. Preparation of test sample solutions: An appropriate amount of the test sample was taken and diluted with 0.85%-0.90% sodium chloride solution so that the aluminum content was 1 mg / mL, and the pH value was adjusted to 6.0-7.0 to prepare the test sample solution. Note that the pH value of different batches of Al-Mn adjuvants of the same type should be adjusted to a fixed value to ensure consistency between different test batches. Bovine serum albumin (also simply called "BSA") solution: An appropriate amount of bovine serum albumin was taken, and a 10 mg / mL solution was prepared using 0.85% to 0.90% sodium chloride solution, and the pH value was adjusted to match that of the test sample solution. Measurement method: Five 15 mL centrifuge tubes were prepared, and 0.08 mL, 0.16 mL, 0.4 mL, 0.8 mL, and 1.2 mL of bovine serum albumin solution (10 mg / mL) was added to each tube. 0.85% to 0.90% sodium chloride solution was added to each tube so that the total volume became 4.0 mL. After mixing well, 1.0 mL of the test sample solution was added to each tube and mixed well. The amount of bovine serum albumin in each tube was 0.8 mg, 1.6 mg, 4 mg, 8 mg, and 12 mg, respectively, and the aluminum element content in each tube was 1 mg. Each tube was left at room temperature for 1 hour (shaking vigorously once every 10 minutes during this time), then centrifuged at 5000g for 10 minutes to collect the supernatant. The free bovine serum albumin content in the supernatant of each tube was measured by the Lowry method (method 2 of General Rule 0731) or other appropriate method, and the absorbance value of each tube was recorded to calculate the protein content. The adsorption rate (A) of each tube was calculated based on the free bovine serum albumin content in the supernatant of each tube corresponding to the total amount of bovine serum albumin. In the calculation, the volume of the supernatant was set to 5 ml. Adsorption rate = (total amount of BSA - amount of supernatant BSA) ÷ total amount of BSA × 100. Results evaluation: The supernatant protein of the two tubes with BSA contents of 0.8mg and 1.6mg should be undetectable, that is, the adsorption rate should not be below 90%. The absorbance values of the tubes with BSA contents of 4mg, 8mg, and 12mg should show an overall increasing trend (if the absorbance value cannot be determined, the supernatant protein content should be detected to determine the overall increasing trend), and the adsorption rate is evaluated as pass.
[0063] (5) 24-hour sedimentation rate: The pH value of the test sample was adjusted to 6.0-7.0 with dilute hydrochloric acid or sodium hydroxide solution, and the test sample was diluted with water so that the aluminum content was 5 mg / mL. If the aluminum content of the test sample was lower than 5 mg / mL, it was diluted to 1 mg / mL with 9 g / L sodium chloride solution after adjusting the pH. If the aluminum content of the test sample was lower than 1 mg / mL, it was left for an appropriate time and the supernatant liquid was discarded so that the aluminum content was 1 mg / mL. Shake for at least 30 seconds, and then take 25 mL of the solution into a graduated cylinder or graduated colorimetric tube and leave for 24 hours. Depending on the amount of precipitated supernatant liquid, the sedimentation rate of the test sample was calculated according to the following formula: Sedimentation rate (%) = Supernatant volume / 25 × 100%.
[0064] In the above examples, the hydrated particle size and surface charge of aluminum hydroxide adjuvant were measured using a nanoparticle size and Zeta potential analyzer (purchased from Malvern, model number Zetasizer Nano ZS). The aluminum content and manganese content of Al-Mn composite adjuvant were measured using an inductively coupled plasma optical emission spectroscopy (ICP-OES, purchased from PerkinElmer, model number PerkinElmer Optima 5300DV). In addition, the adsorption degree and precipitation state were measured with reference to the Chinese Pharmacopoeia (2020 edition). The experimental results are shown in Table 1.
[0065] [Table 1] Example 5
[0066] In the examples of the present application, a comparison of the BMDC activation capabilities of the Al-Mn composite nanocrystals prepared in Examples 1 to 3 is provided as follows.
[0067] The BMDC activation effects of the Al-Mn composite nanocrystals AlMn-001, Al-Mn composite nanocrystals AlMn-002, and Al-Mn composite nanocrystals AlMn-003 prepared in Examples 1 to 3 of the present application were evaluated.
[0068] Immature BMDCs were plated in 6-well plates at 5 × 10 5 The cells were seeded at 1000 cells / well, and cultured in parallel for 24 hours with the commercially available aluminum adjuvant Alum (purchased from Invivogen, CAS: 21645-51-2) with a total metal ion concentration of 50 μg / ml, the Al-Mn composite nanocrystal AlMn-001 obtained in Example 1, the Al-Mn composite nanocrystal AlMn-002 obtained in Example 2, and the Al-Mn composite nanocrystal AlMn-003 obtained in Example 3, three groups per group, and then harvested and stained with anti-CD11c, anti-CD80, and anti-CD86 flow staining solutions. The expression levels of the costimulatory factors CD80 and CD86 on the surface of BMDCs were measured by flow cytometry.
[0069] 5, it can be seen that the dendritic cell activation ability of the Al-Mn composite nanocrystals obtained by implementing the present invention increases with increasing Mn ratio, and the dendritic cell activation ability of the Al-Mn composite nanocrystals AlMn-003 is about twice that of commercially available aluminum adjuvants, indicating that the Al-Mn composite nanocrystals obtained in this application have a superior dendritic cell activation ability. Example 6
[0070] In the examples of the present application, the cell uptake effect after the Al-Mn composite nanocrystals adsorb the antigen is provided as follows. DC2.4 cells were incubated at 37°C in 5% CO 2The cells were cultured in RPMI 1640 medium containing 10% (v / v) FBS in a humid environment at 20 °C. The cells and the constructed nanovaccine (a mixture of 10 mg / L FITC-labeled antigen molecules and 25 mg / L Al-Mn composite nanocrystals AlMn-003 or 100 mg / L commercial aluminum adjuvant Alum (purchased from Invivogen, CAS: 21645-51-2) Alum) were incubated for 8 and 24 hours, respectively. After that, the cells were washed, labeled with Lysotracker Red, fixed and observed under a fluorescent microscope (Perkin Elmer Spinning Disc confocal microscope, 60x oil immersion lens), and images were obtained using UltraVIEW VoX software.
[0071] As shown in FIG. 6, FIG. 6 is a fluorescence imaging image of DC cell entosis after the Al-Mn composite nanocrystal AlMn-003 prepared in Example 3 of the present application or the aluminum adjuvant Alum is bound to an antigen.
[0072] As a result of the experiment, as shown in Figure 6, the Al-Mn composite nanocrystals obtained in Example 3 of the present application were able to carry more antigens into the cells than the commercially available aluminum adjuvant Alum, even when only one-fourth the amount of the commercially available aluminum adjuvant was used. This indicates that the Al-Mn composite nanocrystals obtained in the present application have a better vaccine carrier effect. Example 7
[0073] In the examples of the present application, as described below, verification tests for the immune enhancing effect relationship of the Al-Mn composite nanocrystals obtained in Examples 1 to 3 are provided. Specific tests include the following.
[0074] The Al-Mn composite nanocrystals obtained in Examples 1 to 3 had different Mn:Al molar ratios. The Al-Mn composite nanocrystals with different Mn / Al molar ratios were each injected into mice in combination with OVA antigen, and the titer of the specific antibody produced was measured. The specific method is as follows.
[0075] Experimental animals: Balb / C mice, 6-8 weeks old, 5 mice / group, female. Control group: commercially available aluminum adjuvant Alum (purchased from Invivogen, CAS: 21645-51-2). Dosage: OVA antigen (ovalbumin OVA purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS: 9006-59-1) was 10 μg / mouse, Al-Mn composite adjuvant was 50 μg / 100 μL / mouse, and aluminum adjuvant was 50 μg / 100 μL / mouse. Experimental groups: (1) AlMn-001 (Mn / Al = 0.1), (2) AlMn-002 (Mn / Al = 0.25), (3) AlMn-003 (Mn / Al = 0.375). Immunization regimen: The above drugs were mixed with the antigen in the same volume and injected intramuscularly, and mice were immunized with three injections at three-week intervals. After the mice were immunized in groups, orbital blood was collected on the 19th, 35th, and 56th days. The antibody titers in the serum were measured by ELISA.
[0076] As shown in FIG. 7, the Al-Mn composite nanocrystals with different Mn / Al molar ratios obtained in Examples 1 to 3 not only showed immediate effects after immunizing mice with one injection, but also had a clear positive correlation between the dose-effect relationship. After two immunizations, the dose-effect relationship was still clear. This indicates that the Al-Mn composite nanocrystals have a clear effect on enhancing humoral immunity of OVA vaccine. Example 8
[0077] The examples of the present application provide tests on the Al-Mn composite nanocrystals obtained in Examples 1 to 3 to enhance the immune protective effect of the novel coronavirus SARS-CoV-2 RBD recombinant subunit protein antigen, as follows: Experimental animals: Balb / C mice, 6-8 weeks old, 5 mice / group, female. Dosage: the antigen was 10 μg / mouse, the commercially available aluminum adjuvant Alum (purchased from Invivogen, CAS: 21645-51-2) was 100 μg / 100 μl / mouse, and the AlMn-003 Al-Mn composite nanocrystals was 100 μg / 100 μl / mouse. Experimental groups: (1) novel coronavirus spike protein RBD (also referred to as "RBD antigen", purchased from Sino Biological Company, product number 40592-V08H4); (2) commercially available aluminum adjuvant Alum+RBD; (3) Al-Mn composite nanocrystals obtained in Examples 1 to 3+RBD, namely AlMn-001+RBD, AlMn-002+RBD, and AlMn-003+RBD. Immunization regimen: Mice were immunized using group (1). The other two groups were immunized with commercially available aluminum adjuvant Alum or Al-Mn composite nanocrystal AlMn-003 obtained in embodiment 3, mixed with the antigen in the same volume. The mice were boosted according to the immunization group 3 weeks after the first immunization, and blood was taken from the orbit on the 14th day after the second injection immunization, and the antibody titer in the serum was measured.
[0078] The experimental results showed that the antibody titer still increased with the increase in the proportion of manganese in the Al-Mn composite nanocrystals, and was higher than that of the commercial aluminum adjuvant, as shown in Figure 8. The Al-Mn composite nanocrystals also had good immune-enhancing ability against the new coronavirus subunit protein antigen. Example 9
[0079] The examples of the present application provide a test for enhancing the protective effect of influenza subunit vaccine by the Al-Mn composite nanocrystals obtained in Example 3. Specific tests include the following: The prepared Al-Mn composite nanocrystal AlMn-003 was used as an adjuvant and combined with influenza H1N1 HA antigen to inject into mice, and the titers of specific IgG and IgM antibodies produced were measured. The specific method is as follows:
[0080] Experimental animals: Balb / C mice, 6-8 weeks old, 10 mice / group, female. Dosage: H1N1 HA (purchased from Sino Biological Company, product number 40731-V07H) antigen was 5 μg / mouse, commercial aluminum adjuvant Alum (purchased from Invivogen, CAS: 21645-51-2) was 100 μg / 100 μl / mouse, and AlMn-003 Al-Mn composite nanocrystals was 100 μg / 100 μl / mouse. Experimental groups: (1) H1N1 HA antigen; (2) commercial aluminum adjuvant Alum + H1N1 HA; (3) Al-Mn composite nanocrystal AlMn-003 obtained in Example 3 + H1N1 HA; Immunization regimen: Mice were immunized using group (1). The other two groups were immunized with commercially available aluminum adjuvant Alum or Al-Mn composite nanocrystal AlMn-003 obtained in embodiment 3, mixed with the same volume as the antigen. The mice were immunized according to grouping three weeks after the first immunization, and blood was collected from the orbit two weeks after the second immunization to measure the antibody titer in the serum.
[0081] Serum antibody titers were measured by enzyme-linked immunosorbent assay (ELISA) to assess vaccine-induced IgG and IgM levels in mouse serum. Briefly, 96-well microtitration plates were precoated with H1N1 HA, incubated overnight at 4 °C, and blocked with 2% BSA at 37 °C for 2 h. Then, serially diluted mouse sera were added to the 96-well plates and incubated at 37 °C for 1 h, followed by washing four times with PBS. Bound antibodies were reacted with goat anti-mouse IgG conjugated to HRP for 1 h at 37 °C. After washing four times with PBS, 3,3',5,5'-tetramethylbenzidine (TMB; Sigma) as a substrate was added to the plates and incubated with 0.05% H 2 SO 4 The reaction was terminated by adding 0.5% CO. The absorbance at 450 nm and 630 nm was measured by ELISA (Tecan, San Jose, Calif.).
[0082] FIG. 9 shows the results of analyzing the titers of specific antibodies generated two weeks after the second immunization in mice intramuscularly injected with the Al-Mn composite nanocrystal AlMn-003 prepared in Example 3 of the present application or the commercially available aluminum adjuvant Alum in combination with H1N1 HA antigen at three-week intervals.
[0083] As a result of the experiment, as shown in FIG. 9A, the Al-Mn composite nanocrystals obtained in Example 3 of the present application could enhance immune responses better than commercially available aluminum adjuvants, and the antibody titer generated by the Al-Mn composite nanocrystals was 104 times higher than that of the aluminum adjuvant.
[0084] As a result of the experiment, as shown in FIG. 9B, the Al-Mn composite nanocrystals obtained in Example 3 of the present invention had a higher IgM level than the commercially available aluminum adjuvant, and the antibody titer induced by the Al-Mn composite nanocrystals was three times that of the aluminum adjuvant.
[0085] For the subsequent measurements in Examples 10 to 13, mice immunized with different vaccines in Example 9 were used. 56 days after immunization, five mice were euthanized, spleen and lung tissues were collected, and cell suspensions were prepared for testing to evaluate the immunological efficacy of the vaccines. Example 10
[0086] In the examples of the present application, the T cell test of antigen-specific IFN-γ by ELISPOT is provided after immunizing mice with the Al-Mn composite nanocrystals obtained in Example 3 and the commercially available aluminum adjuvant Alum. Specific tests include: 1) ELISPOT plates were precoated with anti-IFN-γ antibody (5 μg / ml) overnight at 4° C. 2) RPMI1640 medium containing 10% FBS was sealed at room temperature for 2 hours. 3) The spleen of the mouse on day 56 after immunization in Example 9 was ground with 200 mesh gauze to prepare a single cell suspension, and 5 × 10 5 Add 100 cells and incubate at 5% CO 2 and incubated in a 37°C incubator for 24 hours. 4) Biotinylated anti-IFN-γ antibody was added and incubated at room temperature for 2 hours. 5) HRP-crosslinked avidin was added and incubated at room temperature for 1 hour. 6) Using an Immunospot Analyzer ELISPOT reader board, the number of IFN-γ secreting cells (IFN-γ spot-forming cells, SFC) was read using Immunospot software (v.3.0).
[0087] As shown in Figure 10, the experimental results showed that AlMn-003Al-Mn composite nanocrystals promoted γ-IFN secretion by T cells, and the amount of promoted γ-IFN secretion was higher than that of the commercial aluminum adjuvant Alum. The commercial aluminum adjuvant Alum group promoted γ-IFN+ secretion by T cells, and the PBMC ratio was 43.5% compared to the H1N1 HA antigen group. The AlMn-003Al-Mn composite nanocrystal group was 73% of the H1N1 HA antigen group. This indicates that the AlMn-003Al-Mn composite nanocrystals have a superior effect of stimulating cellular immune responses. Example 11
[0088] The examples of the present application provide tests to measure intracellular factors in spleen cells extracted from spleen tissues of mice 56 days after immunization with different vaccines, collected in Example 9. Specific tests include: Flow cytometry was performed by multicolor intracellular cytokine staining assay using spleen cells from mice stimulated with 2 μg / ml protein (H1N1 HA protein). DMSO was used as a negative control (background). Ten million cells were cultured at 37 °C, 5% CO in the presence of Golgistop (BD Biosciences) and Brefeldin A (Sigma). 2The cells were incubated for 6 h at 4°C for 1 h. Cell viability was assessed by measuring intracellular cytokine staining using DAPI-live / dead as a vital dye (Invitrogen) and anti-CD3, anti-CD4, anti-CD8, anti-CD69, anti-CD134, and anti-CD137 as antibodies for surface staining (Biolegend). Cells were permeabilized and stained with anti-IL-2, anti-IL-4, anti-IFN-γ, and anti-TNF-α antibodies (Biolegend). At least 100,000–200,000 lymphocytes were collected by BD LSR Fortessa (BD Biosciences) and analyzed by FlowJo software (Tree Star, Ashland, OR). Samples were defined as positive if the antigen-specific response was at least 3-fold greater than background and at least 0.05% higher than background.
[0089] As shown in Figure 11, the levels of IL-2, IL-4, TNF-α and IFN-γ among the cell factors in the spleen were high, and the level of IL-4 was higher than that of IL-2. Note that IL-2 belongs to Th1 factors, and IL-4 belongs to Th2 factors. This indicates that the Al-Mn composite nanocrystal AlMn-003 according to the present application can promote the secretion of IFN-γ factors that can improve the phagocytic ability of macrophages, and that the Al-Mn composite nanocrystal AlMn-003 can also promote the differentiation of T cells and the maturation of CD8 CTLs. Example 12
[0090] The examples of the present application provide tests of the levels of splenic and lung memory B cells in mice 56 days after immunization with different vaccines in Example 9. Specific tests include the following:
[0091] B cells produce high affinity antibodies, generate immune memory, function as antigen-presenting cells, and secrete cytokines (including CCL22, CCL17, IL-2, IL-4, IL-6, IFN-γ, TNF-α, GM-CSF, IL-10, TGF-β1, and IL-35). Memory B cells and plasma B cells can produce antibodies, such as immunoglobulin (Ig), IgM, IgG, and IgE. Memory B cells are long-lived and remain dormant until they encounter an antigen again. When they encounter an antigen again, they can produce antibodies against that antigen. When they are reexposed to a foreign antigen, memory B cells reactivate and differentiate into plasma cells that can secrete antibodies. IgG homoantibodies are secreted from these plasma cells and have high affinity for a particular foreign antigen. These IgG antibodies efficiently and rapidly neutralize viral and bacterial antigens and become part of a secondary immune response that involves immunological memory, particularly from memory B cells and memory T lymphocytes.
[0092] Therefore, in this application, the memory B cell levels on day 56 of mice immunized with the Al-Mn composite nanocrystal AlMn-003 adjuvant obtained in Example 3 combined with H1N1 HA antigen were evaluated.
[0093] The memory B cell level was measured on the 56th day for mice immunized with the Al-Mn composite nanocrystal AlMn-003 obtained in Example 3 combined with H1N1 HA antigen, and the results are shown in Figure 12. The memory B cell flow results showed that the Al-Mn composite nanocrystal group induced more memory B cells in the spleen and lungs, and had better anti-reinfection ability. Example 13
[0094] The examples of the present application provide a study of splenic memory T cell levels in mice 56 days after immunization with different vaccines in Example 9. Specific studies include the following:
[0095] Considering that memory CD4+ and CD8+ T cells are important components of protective immunity and that effectively inducing memory T cell responses is a primary goal of vaccines against chronic infectious diseases, the present application examined the phenotype of memory T cells in mice 56 days after immunization with the H1N1 HA vaccine.
[0096] Mice were immunized with the Al-Mn composite nanocrystal AlMn-003 obtained in Example 3 in combination with H1N1 HA antigen, and the CD4+T and CD8+T cell levels were measured on day 56. The experimental results are shown in Figure 13. According to the flow chart, the number of memory T cells (Tcm) among CD4+T and CD8+T cells in the spleen was increased in the Al-Mn composite nanocrystal group. Example 14
[0097] The examples of the present application provide the antitumor effect of the Al-Mn composite nanocrystal AlMn-001 obtained in Example 1 as an immunopotentiator. Specifically, the following are included:
[0098] Mice were randomly divided into four groups according to body weight: blank control group (Ctrl), OVA control group, OVA and AlMn-001 (ALMN-001-OVA), and OVA and commercial aluminum adjuvant group (Alum-OVA). According to the experimental design, mice were immunized three times (once every 7 days) and then subcutaneously inoculated with melanoma B16-OVA to establish an orthotopic tumor model. As shown in Figures 14A to 14C, Figure 14A shows the changes in mouse body weight in each group, 14B shows the changes in mouse tumor volume in each group, and 14C shows the survival rate of mice in each group. As shown in Figure 14A, the changes in mouse body weight in each group were not significant. As shown in Figure 14B, on the 20th day, the average tumor size of mice in the control group was 1982 mm 3 In the group immunized with commercial aluminum adjuvant, tumor growth was suppressed to some extent, with the average tumor size being 734.9 mm 3 However, the use of AlMn-001 according to the present application effectively inhibited tumor growth, with the average tumor size in immunized mice decreasing to 201.7 mm 3As shown in Figure 14C, the longest survival time of mice in the control group was 26 days, and the longest survival time of mice immunized with the commercial aluminum adjuvant group was 43 days, while some mice in the AlMn-001 immunized group were still alive on the 65th day, and the survival time of other mice in the group was also obviously extended. This result shows that the use of aluminum adjuvant in advance slightly inhibits tumor growth and slightly improves the survival rate of mice, while the use of AlMn-001 in advance can significantly inhibit tumor growth, significantly improve the survival rate of mice, and significantly extend the survival time. AlMn-001 can be used as a tumor immune effect enhancer to enhance the antigenic tumor effect of the living body. Example 15
[0099] The present application provides a test for combining the Al-Mn composite nanocrystal AlMn-002 obtained in Example 2 with PD-L1 antibody to fight breast cancer distal tumors. Specific tests include the following:
[0100] 100 μL of 4T1 cells (1 × 10 5 ) was inoculated into the right hind leg of Balb / c mice and marked as an orthotopic tumor. The average tumor volume was 100 mm 3 When the tumor volume reached 100 μg / day, the mice were randomly divided into four groups: control group (Ctrl), AlMn-002 group, PD-L1 antibody group (purchased from Biolegend, USA, catalog: 124329, clone 10F.9G2), and AlMn-002-PD-L1 antibody combination group. AlMn-002 was injected via the tail vein (100 μg / subject / mouse). Day 0 was recorded, and the mice in each group were given the corresponding treatment on days 1, 3, and 5, respectively. The tumor volume of the mice in each group was recorded every two days. On day 10, 5 × 10 4 4T1 cells were inoculated into the left hind limb of the mice and recorded as distal tumors. The volumes of the bilateral tumors were kept recorded until day 25.
[0101] The results are shown in Figure 15. Figure 15 shows the therapeutic effect of the combination of Al-Mn composite nanocrystal AlMn-002 and PD-L1 antibody on breast cancer distal tumors. Figure 15 shows that the combination of Al-Mn composite nanocrystal AlMn-002 and PD-L1 antibody not only significantly inhibited the growth of existing tumors, but also significantly inhibited the growth of new tumors. Example 16
[0102] In the examples of the present application, an anti-liver cancer tumor test is provided using the Al-Mn composite nanocrystal AlMn-003 obtained in Example 3 in combination with metformin (Met). Specific tests include the following:
[0103] 100 μL of HepG2 cells (1 × 10 5 ) was inoculated into the right hind leg of Balb / c mice. The average tumor volume was 100 mm 3 When the tumor size reached 100 mm, the mice were randomly divided into four groups: control group (Ctrl), AlMn-003 group, metformin (Met, purchased from Meilunbio, CAS: 657-24-9) group, and AlMn-003-Met combination group. They were injected with AlMn-003 (100 μg / subject / mouse) via the tail vein. Day 0 was recorded, and the mice in each group were given the corresponding treatment on days 1, 3, and 5, respectively. The tumor volume of the mice in each group was recorded every two days.
[0104] The results are shown in Figure 16. Figure 16 shows the therapeutic effect of the combination of Al-Mn composite nanocrystal AlMn-003 and Met antibody on a liver cancer tumor model. Figure 16 shows that the combination of Al-Mn composite nanocrystal AlMn-003 and Met antibody has a clear inhibitory effect on tumor growth in the liver cancer tumor model. Example 17
[0105] The examples of the present application provide a test for the Al-Mn composite nanocrystal AlMn-001 obtained in Example 1 to inhibit the growth of metastatic tumors. Specific tests include the following:
[0106] A mouse 4T1 breast cancer model was established. Tumor-bearing mice were randomly divided into three groups. They were injected intratumorally with (1) saline, (2) paclitaxel (purchased from Shanghai Jiji Biochemical Technology Co., Ltd., CAS: 33069-62-4), and (3) AlMn-001-paclitaxel. Each group received one treatment every two days, and three treatments were performed. On the 10th day, 4 × 10 5 100 μL of PBS containing 4T1 cells was injected into the tail vein. On the 28th day, the mice were killed and the lung tissue was removed. The results are shown in FIG. 17. FIG. 17 shows the effect of treating liver cancer metastasis with AlMn-001 and paclitaxel in combination (the leftmost group is the blank control group, the middle group is the paclitaxel only group, and the rightmost group is the AlMn-001 and paclitaxel combination treatment group). As a result, the lungs of the mice in the blank control group were filled with metastatic tumor lesions, and a certain number of metastatic tumor lesions were seen on the lungs of the mice treated with paclitaxel alone, but almost no tumors were seen on the lungs of the mice treated with AlMn-001. This result indicates that AlMn-001 can be used as an immune enhancer to enhance the anti-metastatic effect of the living body.
[0107] Thus, the Al-Mn composite nanocrystals of the present application have the same ease of use as commercially available aluminum adjuvants, and at a lower concentration than commercially available aluminum adjuvants, have better DC cell activation effects, better antigen presentation effects, better promotion of antigen cell uptake, and lysosomal escape effects, and can simultaneously activate humoral immunity and cellular immunity.Furthermore, they also have the ability to strongly increase the effect of tumor immunotherapy, and can be used as a delivery system for combined immunotherapy agents to improve the effect of immunotherapy.
[0108] It should be noted that the above description is merely a preferred embodiment of the present invention, and that those skilled in the art may make some improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also deemed to be included in the protection scope of the present invention.
Claims
1. A step 1 of mixing an aluminum salt solution, a manganese salt solution, and an anionic auxiliary solution to obtain a mixture, and adjusting the pH of the mixture to 5.5 to 8.5; and step 2, heating the mixture to react with it, and washing the resulting solid product to obtain Al-Mn composite nanocrystals.
2. the solute of the aluminum salt solution is one or more selected from the group consisting of aluminum chloride, aluminum sulfate, aluminum nitrate, and aluminum acetate; The solvent of the aluminum salt solution is one or more selected from the group consisting of sodium acetate solution, physiological saline, water, and ethanol; the solute of the manganese salt solution is one or more selected from the group consisting of manganese chloride, manganese sulfate, manganese nitrate, and manganese acetate; The method according to claim 1 , wherein the solvent of the manganese salt solution is one or more selected from the group consisting of water, physiological saline, and ethanol.
3. the solute of the anionic auxiliary solution is an organic acid salt and / or an amino acid; The method according to claim 1, wherein the solvent of the anionic auxiliary solution is one or more selected from the group consisting of water, physiological saline, and ethanol.
4. the organic acid salt is citric acid or / and salicylic acid, 4. The method according to claim 3, wherein the amino acid is one or more selected from the group consisting of cysteine, cystine, tyrosine, aspartic acid, and glutamic acid.
5. 2. The method according to claim 1, wherein in the mixture, a molar ratio of aluminum element in the aluminum salt solution to manganese element in the manganese salt solution is 1:(0.05-1), and a ratio of a concentration of the anionic auxiliary to a total metal ion concentration (wherein the total metal ion concentration is the sum of the concentrations of the aluminum salt solution and the manganese salt solution) is (0.1-10):
1.
6. The method according to claim 1, wherein in step 2, the heating reaction is carried out at a temperature of 60° C. to 130° C. for a period of 0.5 to 20 hours.
7. An Al-Mn composite nanocrystal, comprising an Al-Mn composite nanocrystal produced by the production method according to any one of claims 1 to 6.
8. Use of the Al-Mn composite nanocrystal produced by the method according to any one of claims 1 to 6 and the Al-Mn composite nanocrystal according to claim 7 in the manufacture of a vaccine adjuvant, an immune enhancer, a pharmaceutical composition, a drug delivery carrier, or an immunogenic composition.
9. 8. An antitumor pharmaceutical composition comprising the Al-Mn composite nanocrystal according to claim 7 and a therapeutic agent for antitumor diseases.
10. A vaccine composition comprising an antigen and the Al-Mn composite nanocrystal of claim 7.
Citation Information
Patent Citations
JP1974074109A
METHOD FOR PRODUCING MnAL ALLOY
WO2018128153A1